2020
DOI: 10.29322/ijsrp.10.05.2020.p101112
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Customers’ Perception towards Service Delivery among Public Service Organizations in Dire Dawa Administration

Abstract: The issue of service delivery is becoming a global concern that demands continuous reform to fit the turbulent environment and changing customer needs. The purpose of this study was therefore to assess customer satisfaction on service delivery of selected public service organizations in Dire Dawa city Administration. The study employed the cross-sectional field survey method since relevant data were collected via at one point in time at public service organizations by distributing questionnaires to customers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Overall, the table revealed that the customers of courier services in Tanza, Cavite agreed on the overall aspects of courier service regarding reliability with a grand mean of 4.19. This result was somehow different from the study conducted by Mengste(2020), which showed that reliability dimension has the lowest score in service quality evaluation.…”
Section: Customer's Evaluation Of Courier Servicescontrasting
confidence: 98%
“…Overall, the table revealed that the customers of courier services in Tanza, Cavite agreed on the overall aspects of courier service regarding reliability with a grand mean of 4.19. This result was somehow different from the study conducted by Mengste(2020), which showed that reliability dimension has the lowest score in service quality evaluation.…”
Section: Customer's Evaluation Of Courier Servicescontrasting
confidence: 98%
“…Generally, in this study it is revealed that the quality of public service delivery factors and customer satisfaction including service quality are highly associated to make positive perception towards the quality service delivery (Kuo, (2003);Zeithaml, (2006); Koirala & Shrestha, (2018); Mengste et al, (2020). Perception towards the customer satisfaction is enhanced when quality service is delivered.…”
Section: Discussionmentioning
confidence: 80%
“…Such result was shown by Agbor, (2011). But theory explains that there is direct relation of quality of public service dimension to perception and satisfaction as opined by Zeithaml, ( 2006) and various results from various research study has also signified such relationship as mentioned by Kuo, (2003); Koirala & Shrestha, (2018): Mengste et al, (2020).…”
Section: Discussionmentioning
confidence: 96%
“…j. (Mengste et al, 2020). Conducted while customer dissatisfaction arises when expectations are not met.…”
Section: Introductionmentioning
confidence: 99%